An update on the diagnosis, treatment, and prognosis of intestinal Behçet's disease. Issue 1 (January 2015) - Cheon, Jae Hee; Kim, Won Ho
Abstract : Purpose of review: This review discusses recent scientific developments in the diagnosis, treatment, and prognosis of intestinal Behçet's disease. Recent findings: Gastrointestinal involvement is a major cause of morbidity and mortality in Behçet's disease. Patient clinical data are scarce because of the rarity of the disease; however, novel diagnostic criteria and disease activity indices have been developed recently to aid treatment of Behçet's disease patients. Current therapies include 5-aminosalicylic acids, corticosteroids, immunomodulators, or antitumor necrosis factor alpha agents. Antitumor necrosis factor alpha agents can achieve clinical responses and remission in patients that were previously nonresponsive to corticosteroids or immunomodulators. Clinical variables, including young age and higher disease activity at the time of diagnosis, volcano-type ulcers, absence of mucosal healing, higher C-reactive protein levels, prior history of surgery, and lack of initial response to medical therapy, can be regarded as poor prognostic factors. Summary: Previously, the diagnosis and management of intestinal Behçet's disease depended upon the expertise of individual clinicians; however, more standardized medical assessments and improved treatment regimens for Behçet's disease patients are evolving.